An exploratory study of m-commerce key benefits and barriers among actual users, intentional users and non-intentional users. Issue 3 (3rd July 2018) - Alduaij, Manal Yousuf
Abstract: The purpose of the study is to explore users' intention to adopt mobile commerce (m-commerce) and to identify users' perceived benefits and perceived barriers that promote or inhibit m-commerce adoption in Kuwait. The study employs a quantitative approach that is based on a sample of 1000 students. Results indicate that user adoption decisions of m-commerce are positively influenced by key benefits more than the key barriers. Key benefits of m-commerce reveal that it is faster, it saves time and it is convenient, useful and handy in all locations. While key barriers of m-commerce range within poor network coverage, slow connection and data transfer, in addition to security risks and privacy of invasion. Theoretical implications show that the technology acceptance model can be applied successfully to examine m-commerce in the context of Kuwait. Practical implications show the benefits and barriers that promote and inhibit m-commerce that, if taken into consideration, can add a competitive advantage to online sellers and small to medium-sized enterprises.